2019
DOI: 10.1016/j.ahj.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference and cardiovascular outcomes: Insights from the Jackson Heart Study

Abstract: Background: Emerging data suggest that neck circumference (NC) is associated with cardiometabolic risk factors. Limited research is available regarding the association between NC and cardiovascular outcomes in African Americans. Methods: Using data from the Jackson Heart Study, we included participants with recorded NC measurements at baseline (2000-2004). Baseline characteristics for the included population were summarized by tertiles of NC. We then calculated age-and sex-adjusted cumulative incidence of clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Several studies have shown an association between NC and elevated BMI, low levels of HDL‐C, elevated triglycerides and insulin resistance biomarkers (insulin, homeostatic model assessment for insulin resistance, etc.) in the adult population 27,28,29,30 . Another study conducted with healthy adult Brazilians participating in the Longitudinal Study of Adult Health (ELSA‐Brasil) showed that NC presented a significant and independent association with high TGL and low HDL‐C, as well as other cardiometabolic risk factors 31 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown an association between NC and elevated BMI, low levels of HDL‐C, elevated triglycerides and insulin resistance biomarkers (insulin, homeostatic model assessment for insulin resistance, etc.) in the adult population 27,28,29,30 . Another study conducted with healthy adult Brazilians participating in the Longitudinal Study of Adult Health (ELSA‐Brasil) showed that NC presented a significant and independent association with high TGL and low HDL‐C, as well as other cardiometabolic risk factors 31 …”
Section: Discussionmentioning
confidence: 99%
“…Neck fat, as an ectopic fat depot, is likely to play a role in accelerating atherosclerosis in the vessels of the neck through direct paracrine action, which leads to an increased risk of CVD compared with the risks associated with systemic and central obesity 7‐11 . Baena et al 7 performed ultrasound assessments of C‐IMT in a multicenter prospective cohort and found that there was a positive correlation between NC and C‐IMT in both men and women; moreover, the correlation remained significant after adjusting for age, race, hypertension, diabetes, dyslipidemia, smoking, BMI, and WC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a close correlation between subcutaneous fat accumulation in the upper body and obesity‐related CVD was found, which made NC likely to be a powerful and simple tool for identifying cardiovascular diseases. Previous studies have revealed that NC is closely related to atherosclerosis, stroke and CVD 7‐11 . However, the correlation between NC and subclinical atherosclerosis is not yet clear.…”
Section: Introductionmentioning
confidence: 96%
“…The measurement of NC is simple without exposure of the abdomen and minimally affected by breathing and diet, with an explicit anatomic landmark, high repeatability, and low variability. Accumulating studies have confirmed that NC, similar to WC, is a powerful tool for determining obesity or metabolic syndrome and predicting the risks of cardiovascular diseases 13‐15 . Our previous study found that the optimal cut‐off point of NC for the identification of metabolic syndrome was 34.5 cm in women by measuring the visceral fat area using magnetic resonance imaging and accurately evaluating central obesity 15 .…”
Section: Introductionmentioning
confidence: 92%